Factors influencing physical activity in pregnancy : a systematic review - Idayu Badilla Idris,; Sharifah Fazlinda SN,; Norain A,; Noor Atika A,; Azmawati Mohammed Nawi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Lack of physical activity in pregnancy may lead to poor maternal and perinatal outcomes including gestational diabetes, hypertensive disorders and postpartum depression. Given these risks, identifying factors that influence physical activity in pregnancy is crucial to planning and implementing appropriate interventional programmes and managing this vulnerable group. Peer reviewed articles on factors influencing physical activity in pregnancy were searched using the Pub-Med and Ovid databases, from 2014 to 2019. The selected articles were reviewed by two authors and critically appraised using the Mixed Methods Assessment Tool 2018. A total of 16 articles were included. Factors that positively influenced physical activity in pregnancy were fun, higher economic status, early trimester, and higher body weight. Factors that negatively influenced physical activity in pregnancy were lack of knowledge, lack of social support, multiparity, physical pain and discomfort, ethnic minority status, and concern for the safety of the baby. Fun was one of the most reported motivators of physical activity in pregnancy, and the most reported reason for reduced physical activity was lack of knowledge. Additionally, social support from friends and family played an important role in encouraging pregnant women to be active. This systematic review highlights the need to improve current health education programmes for physical activity in pregnancy, which should ideally be extended and targeted to the whole community, beyond pregnant women themselves for better uptake and acceptance.